Global and local sources of risk in Eastern European emerging stock markets - Elena Fedorova; Mika Vaihekoski (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
We study a pricing model for global and local sources of risk in six Eastern European emerging stock markets. Utilizing GMM estimation and an unconditional asset-pricing framework with and without time-varying betas, we perform estimations based on monthly data from 1996 to 2007 for Poland, Czech Republic, Hungary, Bulgaria, Slovenia and Russia. Most of these markets display considerable segmentation; the aggregate emerging market risk, as opposed to global market risk, is the significant driver for their stock market returns. It also appears that currency risk is priced into stock prices. The difference between local and global interest rates can be used to model the time-variation in the betas for both sources of risk.
URN:NBN:fi:bof-201408072061
Keywords: G12; G15; G32; 330; market integration; segmentation; asset pricing; emerging markets; Eastern Europe country risk